International spillovers, productivity growth and openness in Thailand: an intertemporal general equilibrium analysis - Diao, Xinshen; Rattso, Jorn; Stokke, Hildegunn Ekroll (Elsevier, 2005)
Thailand has experienced economic growth well above world averages from 1960 to the recent crisis. While the controversy over Thailand and East Asian growth has discussed the role of capital accumulation versus productivity, we analyze the general equilibrium interaction between productivity and investment in an intertemporal growth model. The high growth is understood as a prolonged transition path with gradual tariff reduction and endogenous productivity driven by foreign spillover feeding capital investment. Counterfactual analyses show how protection would have reduced growth with productivity and investment slowdown, while shock liberalization would have raised immediate growth with faster convergence to steady state.